2014
DOI: 10.1093/gerona/glu086
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Lipid Content and Oxidative Activity in Relation to Muscle Fiber Type in Aging and Metabolic Syndrome

Abstract: One of the most noticeable effects of aging is the reduction in skeletal muscle mass and strength (sarcopenia). The metabolic syndrome (MS) is also prevalent in old subjects, but its relevance to skeletal muscle characteristics has poorly been investigated. Immunohistochemical studies were performed with muscle biopsies from young (22 years) and old (73 years) men with and without MS to reveal age-dependent and MS-associated modifications of fiber-type characteristics. Atrophy of type II fibers and altered fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 45 publications
8
105
0
2
Order By: Relevance
“…In fact, supporting a causal effect of insulin resistance on sarcopenia in the elderly, induction of insulin resistance in old rats by sucrose feeding results in significant loss of lean body mass, increase in fat mass and reduced muscle protein synthesis (Gatineau et al, 2015). The alteration of skeletal muscle by insulin resistance is further suggested by the altered muscle fiber type content and the increased accumulation of intramyocellular lipid droplets in muscle biopsies from elders with metabolic syndrome (Gueugneau et al, 2015).…”
Section: Diabetesmentioning
confidence: 99%
“…In fact, supporting a causal effect of insulin resistance on sarcopenia in the elderly, induction of insulin resistance in old rats by sucrose feeding results in significant loss of lean body mass, increase in fat mass and reduced muscle protein synthesis (Gatineau et al, 2015). The alteration of skeletal muscle by insulin resistance is further suggested by the altered muscle fiber type content and the increased accumulation of intramyocellular lipid droplets in muscle biopsies from elders with metabolic syndrome (Gueugneau et al, 2015).…”
Section: Diabetesmentioning
confidence: 99%
“…Functional muscle overload causes a gain in muscle mass while prolonged exercise leads to the transformation of pre-existing fast-twitch muscle fibers to a slow-twitch oxidative phenotype. Type IIb fibers, the most powerful fibers, are converted to oxidative phenotype fibers (type I or IIa) and disappear through a necrotic process during myopathies, aging, and glucocorticoid treatments [18, 19] . Intracellular/cytosolic Ca 2+ ([Ca 2+ ] i ) fluctuations play a crucial role in the maintenance and adaptation of muscle phenotypes.…”
Section: Muscle Phenotype and Rankmentioning
confidence: 99%
“…Previous investigations based on human biopsies indicated that muscle aging (sarcopenia) is associated with important modifications at the fiber-type level. Specifically, MALDI-MSI provided evidence for aging- and metabolic syndrome-dependent alterations in intra-myofibrillar lipids [2]. Using small human biopsies, MSI of proteins could be less sample-consuming than usual analytical techniques, such as two-dimensional gel electrophoreses [3] or shot-gun proteomics [4].…”
Section: Introductionmentioning
confidence: 99%